2017
DOI: 10.3892/mco.2017.1462
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms of long non‑coding RNA PRNCR1 and prostate cancer risk in a sample of the Iranian population

Abstract: Abstract. The aim of the present study was to determine whether there is an association between the long non-coding RNA (lncRNA) prostate cancer-associated non-coding RNA 1 (PRNCR1) polymorphisms and prostate cancer (PCa) risk in a sample of the Iranian population. This case-control study was performed on 178 patients with PCa and 180 subjects with benign prostatic hyperplasia (BPH). Genotyping assay was performed by polymerase chain reaction-restriction fragment length polymorphism. The findings indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 70 publications
(63 reference statements)
0
21
1
Order By: Relevance
“…PRNCR1 acts as a ceRNA by sponging miR-448 to modulate HEY2 [68]. It has been shown that there was a significant correlation between the rs13252298, rs1456315, and rs7841060 genetic polymorphisms of PRNCR1 and increased risk of PCa in a sample of the Iranian population [66]. The PRNCR1 polymorphisms were also associated with gastric cancer risk among Korean and Chinese Populations [69,70].…”
Section: Prostate and Bladder Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…PRNCR1 acts as a ceRNA by sponging miR-448 to modulate HEY2 [68]. It has been shown that there was a significant correlation between the rs13252298, rs1456315, and rs7841060 genetic polymorphisms of PRNCR1 and increased risk of PCa in a sample of the Iranian population [66]. The PRNCR1 polymorphisms were also associated with gastric cancer risk among Korean and Chinese Populations [69,70].…”
Section: Prostate and Bladder Cancersmentioning
confidence: 99%
“…Prostate cancer associated non-coding RNA 1 (PRNCR1) is located in 8q24.21 and highly expressed in aggressive PCa. It has a critical role in PCa progression through regulation of androgen receptor (AR) [66]. Besides, the PRNCR1 acts as an oncogene in colorectal cancer [67] and gastric cancer [68].…”
Section: Prostate and Bladder Cancersmentioning
confidence: 99%
“…Although previously proposed as a novel biomarker of disease progression, considering the essential role of NEAT1 in ER signaling pathway, NEAT1 might pose as a novel therapeutic target for the treatment of PCa (9). The lncRNA PCa-associated non-coding RNA 1 (PRNCR1), also referred to as PCAT8 and CARLo3, is mapped to 8q24.21 (10). Upregulation of PRNCR1 is associated with PCa development via modulation of AR activity.…”
Section: Role Of Lncrnas In Prostate Cancermentioning
confidence: 99%
“…The impact of PRNCR1 polymorphisms on the risk of developing different types of cancers, such as prostate (11), gastric (12) and colorectal cancer (13) has been investigated. A recent study on the impact of PRNCR1 variants on risk of PCa showed that the PRNCR1 rs13252298, rs1456315 and rs7841060 polymorphisms could be used as a biomarker for PCa development (10). Understanding the mechanisms involved in AR activation in the milieu of low androgen may be crucial for favorable treatment of castration-resistant PCa (CRPC).…”
Section: Role Of Lncrnas In Prostate Cancermentioning
confidence: 99%
“…An accumulating number of lncRNAs have been demonstrated to be associated with breast cancer initiation and progression, thus suggesting that functional elucidation of key lncRNAs in breast cancer cells may provide valuable information for clinical screening and management. Prostate cancer-associated ncRNA 1 (PRNCR1) is closely associated with resistance of prostate cancer to castration (15), colorectal cancer cell proliferation and cell cycle progression (16), and progression of other types of cancer (17). However, to the best of our knowledge, the implications of PRNCR1 in breast cancer progression have not been previously addressed.…”
Section: The Novel Long Non-coding Rna Prncr1-2 Is Involved In Breastmentioning
confidence: 99%